SCHEDULING EVALUATION OF CONSTRUCTION PROJECT USING FUZZY LOGIC APPLICATION FOR SCHEDULING (FLASH) METHOD - Hasugian, Devina Bianca Putri Rahadyan; Maharani, Aditya; Rachman, Farizi (Universitas Maarif Hasyim Latif, 2024)
For the running of a project, it is necessity to have project planning such as project schedule. PT Ometraco Arya Samanta is a company that engaged in steel structure. This company implement schedule planning based on tonnage. This method is considered suboptimal, since in its implementation has discrepancy of completion time between the schedule plan and the actual. To get an optimal schedule, it needs appropriate method. Construction project is a complex project and has uncertainty completion time. Project Evaluation and Review Technique (PERT) and Fuzzy Logic Application for Scheduling (FLASH) could be used for projects with uncertain completion time and more emphasis on time estimation than cost. PERT and FLASH are using three estimation time, then obtained probability percentage of completion time. Nevertheless, PERT is only consider the completion time by the critical path, while FLASH is able to determine project time by the entire project activities. Thereby, the methods used in this article is FLASH. The analysis results of this case study as follows: the interval completion time with FLASH in the amount of 106 days for optimistic time, 237 days for pessimistic time, and 169 days for most likely time. By the duration target of 179 days, it is obtained 85,29%. Dalam pengerjaan suatu proyek diperlukan perencanaan proyek berupa penjadwalan proyek. PT Ometraco Arya Samanta merupakan perusahaan konstruksi baja. Perusahaan ini memanfaatkan penjadwalan berdasarkan tonase proyek. Metode tersebut dirasa belum optimal, sebab dalam pelaksanaannya sering kali terjadi ketidaksesuaian waktu penyelesaian proyek antara rencana dengan aktualnya. Untuk mendapatkan penjadwalan yang optimal, diperlukan metode yang tepat. Proyek konstruksi merupakan proyek yang kompleks dan memiliki durasi penyelesaian yang bersifat tidak pasti. Project Evaluation and Review Technique (PERT) dan Fuzzy Logic Application for Scheduling (FLASH) dapat digunakan untuk proyek yang memiliki ketidakpastian waktu dan menekankan pada estimasi waktu daripada biaya. PERT dan FLASH menggunakan tiga estimasi waktu yang kemudian didapatkan persentase kemungkinan terselesaikannya proyek. Namun, PERT hanya memperhitungkan waktu penyelesaian proyek berdasarkan lintasan kritis, sedangkan FLASH dapat mempertimbangkan waktu proyek dari keseluruhan kegiatan proyek. Sehingga, metode yang digunakan di dalam artikel ini adalah FLASH. Hasil analisis dari penelitian ini didapatkan selang waktu penyelesaian proyek yaitu waktu paling cepat 106 hari, waktu paling lama 237 hari, dan waktu paling mungkin sebesar 169 hari. Dengan menggunakan waktu target 179 hari, didapatkan probabilitas sebesar 85,29% dari rentang waktu 169 hari hingga 237 hari.